THE EFFECT OF THE SELF-DIRECTED DIALOGUE TOWARD SPEAKING ABILITY FOR STUDENTS AT ELEVENTH GRADE OF SMA TAMAN SISWA PEMATANG SIANTAR - Marhaeni K. D. Matondang; Anita Purba; Tutiariani Nasution; Fellya Putri Sitohang (Jurnal Scientia, 2023)
The aim of this research was to find out the Influence of the self directed dialogue toward speaking ability of the students eleventh grade in the academic year of 2021/2022 at SMA Taman Siswa Pematang Siantar. This research was conducted on June 2022. This research was classified as a true-experimental study. It involved 66 students from two groups, as the experimental group (30 students) and as the control group (36 students). The experimental group was students taught using self directed dialogue where as the control group was students taught using lecture technique. The data were obtained by using pre-test and post-test. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistic. (SPSS 22.0). The result of the research shows that the testing hypothesis of post-test score, it is found that tcount (6,981) > ttable (2,373) at the significance level a = 0.05 and degrees of freedom (df) = 29. H0 is rejected and Ha is accepted. So, it means that the self directed dialogue strategy effect significantly to improve students’ speaking ability of the students eleventh grade in academic year of 2021/2022 at SMA Taman Siswa Pematang Siantar.